Kebijakan Tax Amnesty: Suatu Peninjauan dalam Perspektif Etika Deontologi Sebagai Bentuk Pilihan Wajib Pajak dalam Melaksanakan Kewajiban Perpajakan - Indra Lila Kusuma; Maya widyana Dewi (Jurnal Akuntansi dan Pajak, 2018)
This research aim to know Tax Amnesty In Perspective Deontology Ethics. This research is a qualitative research that is analytic descriptive with focused on one phenomenon only chosen and want to be understood deeply by ignoring other phenomena, in this case that is implementation of Tax Amnesty policy. This study uses data analysis techniques in the form of data presentation techniques. That is the activity when a set of information is compiled, thus giving the possibility of drawing the conclusion of the form of presentation of qualitative data in the form of narrative text. To answer the formulation of the problem that is about tax amnesty in the perspective of deontology ethical theory, the researcher uses some literature of literature that come from various sources related to the discussion that want to be examined in this research such as books, scientific journals, electronic media, and mass media update. The results of this study indicate that the application of tax amnesty if viewed from the perspective of deontology ethical theory has been running well with followed by the taxpayer as a liability without seeing the final results of good and bad for the taxpayer self. This is evidenced by the successful implementation of tax amnesty in the form of increased tax revenue with total assets reported consisting of domestic property declaration Rp 3.676 trillion and declaration of foreign property reached Rp 1.031 trillion. While the withdrawal of funds from abroad (reptriation) reached Rp 147 trillion.